Sistem Pendukung Keputusan Program Keluarga Harapan (PKH) Berbasis Analytic Network Process (ANP) Desa Sepang Kelod - Ni Ketut Deni Julia Marlina; Agus Aan Jiwa Permana; I Nyoman Wahyu Wijaya Kusuma (Lembaga Yasin AlSys, 2026)
The Family Hope Program is one of the government social assistance programs aimed at helping underprivileged communities. However, the process of determining recipients of Family Hope Program assistance in Sepang Kelod Village is still carried out manually through deliberation or village meetings, which has the potential to create subjectivity in decision-making. This study aims to design and implement a Decision Support System for Family Hope Program assistance recipients using the Analytic Network Process method. This study developed a web-based system used to manage community data and conduct the eligibility calculation process for prospective assistance recipients based on ten predetermined assessment criteria. The calculations were performed using Super Decisions software to determine criterion weights and the priority of alternative assistance recipients. The results show that the developed Decision Support System was able to generate rankings of prospective Family Hope Program assistance recipients based on scores from the calculation process using the Analytic Network Process method. This method was able to produce priority alternatives for assistance recipients more systematically based on the weight of each criterion. The conclusion of this study affirms that the implementation of a web-based Decision Support System using the Analytic Network Process method can assist Sepang Kelod Village officials in determining Family Hope Program assistance recipients more objectively, efficiently, and based on data. The implications of this study show the importance of utilizing decision-making technology to improve the accuracy, transparency, and accountability of social assistance management at the village level.